Mechanical and tribological behavior of red clay ceramic tiles coated with fly ash powders by thermal spraying technique (2017)
ABSTRACT: The mechanical and tribological performance of red clay ceramic tiles uncoated and coated by oxy-fuel thermal spraying process from fly ash powders was evaluated. The ceramic tile substrates were manufactured by uniaxial pressing at 26.17 bar pressure, and sintered at 1100 °C. The coating thickness was determined based on the number of projection-cycles oxyacetylene flame over substrate. Coal fly ash coatings were deposited, with average thickness of 56.18±12.18 μm, 180.42±20.32 μm, and 258.26±25.88μm. The mechanical resistance to bending and wear by abrasion deep, were studied using ISO 10545-4 standards and ISO 10545-6 respectively; adhesion was measured using Elcometer equipment Type III according to ASTM D-4541-02 and the average roughness (Ra) was found according to ASTM standard D7127-13, using the profilometer Mitutoyo SJ 201. The surface morphology presented the heterogeneous molten or semi molten splats with average size of 35.262±3.48 micrometers with good adhesion, justifying increased mechanical resistance to bending by 5%, as well as wear by abrasion deep. These results contribute to the development of ceramic products with added value, to be used in various technological applications.